Social Cognition in a Clinical Sample of Personality Disorder Patients - Ruiz-Tagle, Amparo; Costanzo, Elsa; De Achával, Delfina; Guinjoan, Salvador (Frontiers in Psychiatry, 2015)
Social cognition was assessed in a clinical sample of personality disorder (PD) stable patients receiving ambulatory treatment (N = 17) and healthy matched controls (N = 17) using tests of recognition of emotions in faces and eyes, in a test of social faux pas and in theory of mind (ToM) stories. Results indicated that when compared with healthy controls, individuals with PD showed a clear tendency to obtain lower scoring in tasks assessing recognition of emotion in faces (T = −2.602, p = 0.014), eyes (T = −3.593, p = 0.001), ToM stories (T = −4.706, p = 0.000), and Faux pas (T = −2.227, p = 0.035). In the present pilot study, PD individuals with a normal cognitive efficiency showed an impaired performance at social cognition assessment including emotion recognition and ToM.